The carbon impact of a UK safari park – Application of the GHG protocol using measured energy data. (15th June 2018) - Finnegan, Stephen; Sharples, Steve; Johnston, Tom; Fulton, Matt
Abstract: Determining the carbon impact of commercial developments is an essential starting point in understanding a company's carbon footprint. It is also integral to the development of a strategy to reduce that impact in a cost effective manner. There are numerous industry standard carbon calculation methodologies. This paper focuses on the application of one such method, the Greenhouse Gas (GHG) Protocol, and applied it to the unusual example of a UK safari park. The safari park management wanted to understand the park's impact on the environment as part of a long-term plan to reduce that impact by identifying realistic carbon reduction solutions. Actual monitored energy data for a twelve-month period were available as part of the analysis. The results of this paper show that the application of the GHG Protocol, in reality, and especially for a non-standard situation, is difficult. Effective performance monitoring is essential to enable transparent recording of data, from which a carbon footprint can be calculated. The methodologies for calculation are relatively straightforward but depend upon available information. Identification of the carbon impact of the development is the relatively easier task - the real challenge is reducing this impact to near zero in a cost effective manner. Highlights: There remains a lack of information on the carbon impact of safari parks. Application of the GHG Protocol for non-standard situations is difficult. Identification of the carbon impact of any development is relatively easy if data is readily available. The real challenge of reducing the carbon impact is to do so in a cost effective manner.